Mixed Matrix Membrane Incorporating of MgAl-CO3 Layered-Double-Hydroxide for Enhanced Carbon Dioxide Separation. Issue 1 (April 2021) - Fajrina, N.; Yusof, N.; Ismail, A.F.; Jaafar, J.; Aziz, F.; Salleh, W.N.W.; Ismail, N.M.
Abstract: In this study, mixed matrix membranes were fabricated by incorporating MgAl-CO3 layered double hydroxides (LDH) into polysulfone (PSF) coated with low-cost commercial PEBAX polymer for enhancing CO2 /CH4 separation. LDH was synthesized via a simple co-precipitation method and flat sheet membranes were fabricated by dry/wet inversion phase. The gas separation performance on pure PSF and LDH/PSF membranes were investigated. The physical property, chemical structure and membrane morphology were characterized by XRD, FTIR, and SEM. The sample membranes were tested with CO2 and CH4 gas for permeance performance and selectivity of CO2 /CH4 was calculated. By incorporation of LDH, the CO2 permeance increased about 54.6%. LDH mixed matrix membranes displayed the 18.2 GPU of CO2 permeance and CO2 /CH4 selectivity of 18.0. The LDH based membrane produces innovation in membrane technology by improving its morphology and permeance performance with great potential for large-scale CO2 capture and separation.